Factors That Influence Repurchase Intention: A Systematic Literature Review - Muhammad Amfahtori Wijarnoko; Edwin Pramana; Joan Santoso (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2023)
This research is a systematic literature review of factors that influence repurchase intention. Repurchase intention is important for companies because it will shape customer behavior to become loyal, customers usually tend to have an interest in buying products or services repeatedly so that the company will benefit from products or services that have been sold. The aim of this research is to provide insights into the research trends and issues in the studies of Repurchase Intention. The literature search focused on finding journals published between 2018 and 2023. Only English-language journals with the keyword Repurchase Intention were used in this research. Researchers found 80 journals that matched these keywords but after reading the collected articles thoroughly and removing duplicate and irrelevant articles, the authors produced 50 articles to be used in this research. The findings highlight key drivers for increasing sales: Satisfaction, Trust, Perceived Value, Price, and Word of Mouth. Additionally, 14 moderating factors were identified, with Age being the most prominent in four articles. Korea, India, and Indonesia lead research contributions, each with six articles. Structural Equation Modeling (SEM) is the prevailing measurement method, while other approaches persist. Companies are recommended to prioritize these core factors for consumer engagement. Future research should delve into unexplored moderating factors and alternative measurement methods, enriching our understanding of this vital field.